Demineralized dentin matrix for bone regeneration in dentistry: A critical update - Zohaib Khurshid; Necdet Adanir; Jithendra Ratnayake; George Dias; Paul R. Cooper (Saudi Dental Journal)
Over the last few decades, several new materials and techniques have been developed for bone regeneration. Scaffolds based on demineralized dentin matrix (DDM) present an attractive option due to their availability and several animal and human studies have been conducted to ascertain their utility in regenerative dentistry. The aim of this review was to summarize the recent studies conducted on DDM and used for bone grafts. PubMed, Web of Science, and Scopus were used to search for studies published within the last 10 years. The keywords and terms used were: “demineralized dentine matrix”, “bone grafting”, “bone augmentation” and “guided tissue regeneration” in various combinations. Original studies (in vitro, animal and human) and systematic reviews were included in the literature search. The literature search initially identified 23 studies (16 animal studies and 7 clinical reports. Most studies included in this review indicate that DDM has demonstrated promising results in a variety of dental and regenerative medicine applications. Further studies are required to completely comprehend its characteristics and prospective applications. Future studies should also focus on optimizing the processing protocols for the production of DDM-based scaffolds.